Early-Life Nutrition Interventions Improved Growth Performance and Intestinal Health via the Gut Microbiota in Piglets - Luo, Chengzeng; Xia, Bing; Zhong, Ruqing; Shen, Dan; Li, Jiaheng; Chen, Liang; Zhang, Hongfu (Frontiers in Nutrition, 2022)
Intestinal infections in piglets are the main causes of morbidity before and after weaning. Studies have not explored approaches for combining pre-weaning and post-weaning nutritional strategies to sustain optimal gut health. The current study thus sought to explore the effects of early-life nutrition interventions through administration of synthetic milk on growth performance and gut health in piglets from 3 to 30 days of age. Twelve sows were randomly allocated to control group (CON) and early-life nutrition interventions group (ENI). Piglets were fed with the same creep diet from 7 days of age ad libitum. Piglets in the ENI group were provided with additional synthetic milk from Day 3 to Day 30. The results showed that early-life nutrition interventions improved growth performance, liver weight, spleen weight, and reduced diarrhea rate of piglets after weaning (P < 0.05). Early-life nutrition interventions significantly upregulated expression of ZO-1, Occludin, Claudin4, GALNT1, B3GNT6, and MUC2 in colonic mucosa at mRNA level (P < 0.05). Early-life nutrition interventions reduced activity of alkaline phosphatase (AKP) in serum and the content of lipopolysaccharides (LPS) in plasma (P < 0.05). The number of goblet cells and crypt depth of colon of piglets was significantly higher in piglets in the ENI group relative to that of piglets in the CON group (P < 0.05). The relative mRNA expression levels of MCP-1, TNF-α, IL-1β, and IL-8, and the protein expression levels of TNF-α, IL-6, and IL-8 in colonic mucosa of piglets in the ENI group were lower compared with those of piglets in the CON group (P < 0.05). Relative abundance of Lactobacillus in colonic chyme and mucosa of piglets in the ENI group was significantly higher relative to that of piglets in the CON group (P < 0.05). Correlation analysis indicated that abundance of Lactobacillus was positively correlated with the relative mRNA expression levels of ZO-1, Claudin4, and GALNT1, and it was negatively correlated with the level of MCP-1 in colonic chyme and mucosa. In summary, the findings of this study showed that early-life nutrition interventions improved growth performance, colonic barrier, and reduced inflammation in the colon by modulating composition of gut microbiota in piglets. Early-life nutrition intervention through supplemental synthetic milk is a feasible measure to improve the health and reduce the number of deaths of piglets.